Synthesis of Assigned Structure of Cairomycin A, 6-Isopropyl-2,5-Diketopiperazine-3-Acetic Acid and Its Β-Lactam Analogue N`- (3-Methyl-1-Hydroxybutyr-2-Yl) Azetidin-2-One-4-Carboximide - Hussain, Faiq H. S. (Science Journal of University of Zakho, 2019)
In the present investigation, the research carried out into the total synthesis of the assigned structure of cairomycin A, 6-isopropyl-2,5-diketopiperazine-3-acetic acid from its precursors L-valine and L-aspartic acid, and its analogue N`-(3-methyl-1-hydroxybutyr-2-yl)azetidin-2-one-4-carboximide from 4-vinylazetidi-2-one through two different sequence reactions. Structures of the synthesized products were identified by using chemical and physical methods such as elemental analysis, IR, 1H-NMR and MS. The obtained results were compared with those reported, it was found that neither of the synthesized compounds was Cairomycin A.